Evaluation of the Safety and Efficacy of a Low-Temperature Plasma Surgical System for Pterygium. Issue 12 (December 2020) - Huang, Haixiang; Li, Saiqun; Zhong, Jing; Wang, Bowen; Peng, Lulu; Deng, Yuqing; Wang, Mingwu; Yuan, Jin
Abstract : Purpose: Surgical excision is the standard treatment for pterygium. This study was conducted to evaluate the safety and efficacy of a novel technique using low-temperature plasma (LTP) for excision and hemostasis in pterygium surgery. Methods: A prospective, comparative, and randomized clinical trial was conducted on 60 patients (60 eyes) undergoing pterygium excision with conjunctival autografts using fibrin glue. Patients were equally divided into the following 2 groups: a control group and a LTP group. Postoperative follow-up visits were scheduled on day 1, week 1, and months 1 and 3, and recurrence was evaluated at 1 year. Patients were examined for operative time, best corrected visual acuity, conjunctival autograft inflammation (CAI), graft stability (GS), pain, recurrence, and final appearance. Factors related to pterygium recurrence and final appearance were analyzed. Results: Mean operative times were shorter in the LTP group (16.7 ± 3.4 min) than those in the control group (20.1 ± 4.7 min, P = 0.002). LTP eyes had milder CAI than control eyes at postoperative day 1 ( P = 0.000) and week 1 ( P = 0.000). Patients in the LTP group exhibited better GS ( P = 0.01) and milder pain ( P = 0.04) than those in the control group on day 1. Two control patients (6.7%) and no (0%) LTP patients experienced recurrence ( P = 0.08). GS and CAI were the significant factors contributing to recurrence (GS: R = 0.425, P = 0.001; CAI: R = 0.309, P = 0.016). Conclusions: LTP to replace surgical blades and disposable cautery for ablation and hemostasis is safe and efficient for pterygium surgery, resulting in shorter operative time, milder inflammation, and better graft stability without increasing complication risk.